The effect of extending graduated driver licensing to older novice drivers in Indiana. (September 2020) - Wang, Yudan Chen; Foss, Robert D.; Goodwin, Arthur H.; Curry, Allison E.; Tefft, Brian C.
Highlights: Examined the effects of Indiana's GDL update on older novice drivers aged 18–21. Crash data and licensing data from Indiana were utilized. There was no evidence to suggest that the GDL update reduced nighttime and passenger-involved crashes for older novices. Abstract: Introduction : Graduated driver licensing (GDL) systems have been shown to reduce rates of crashes, injuries, and deaths of young novice drivers. However, approximately one in three new drivers in the United States obtain their first driver's license at age 18 or older, and thus are exempt from most or all provisions of GDL in most states. Method: In July 2015, the state of Indiana updated its GDL program, extending its restrictions on driving at night and on carrying passengers during the first 6 months of independent driving, previously only applicable to new drivers younger than 18, to all newly-licensed drivers younger than 21 years of age. The current study examined monthly rates of crashes per licensed driver under the affected conditions (driving at night and driving with passengers) among Indiana drivers first licensed at ages 18, 19, and 20 under the updated GDL system compared with drivers licensed at the same ages under the previous GDL system. We used Poisson regression to estimate the association between the GDL system and crash rates, while attempting to control for other factors that might have also influenced crash rates. We used linear regression to estimate the association between the GDL system and the proportion of all crashes that occurred under conditions restricted by the GDL program. Results: Results showed, contrary to expectations, that rates of crashes during restricted nighttime hours and with passengers were higher among drivers licensed under the updated GDL system. This mirrored a statewide increase in crash rates among drivers of all ages over the study period and likely reflected increased overall driving exposure. The proportions of all crashes that were at night or with passengers did not change. Practical Applications : More research is needed to understand how older novice drivers respond when GDL systems originally designed for younger novice drivers are applied to them.